An analysis of the effect of English proficiency towards students' academic performance in university of Malaysia Sabah - Qhatrunnada Suyansah; Darmesah Gabda (2020)
Students are the main assets of universities. Students’ academic performance has been the top priority for themselves, educators, researchers, government, and parents. There have been many studies that sought to investigate factors that influence students’ academic performance and they discover that hard work, discipline, class attendance, self-motivation, previous schooling and family’s income affect students’ academic performance, and these seem to have significant effects on the students’ final Cumulative Grade Point Average, CGPA. This study aims to investigate whether students’ English language results and their entry results during admission are also factors that influence their final Cumulative Grade Point Average, CGPA. Multiple linear regression was the analysis used to determine the effect of English proficiency towards students’ academic performance. Thus, the results will show the factors that significantly contribute to the students’ academic performance.